Analysis of Educator and Education Personnel Standards in Indonesia - Ramadhan, Fitri Nur; Lanasari, Rossy; Cahyani, Septia Dwi; Nurjayadi, Muktiningsih; Ridwan, Achmad (Jurnal Inovasi Pendidikan MH Thamrin, 2025)
Education is an absolute necessity for everyone to have high competitiveness, especially in the current era of globalization, without having adequate competitiveness, it is difficult for a person to face increasingly competitive labor competition. The aim of this research is to determine the functions and problems of standardization of educators and education personnel in Indonesia. The method used in this research is qualitative library research, namely a type of research that refers to literary treasures such as book literature, laws, government regulations, articles and e-journals. The research results show that the function of standardizing educators and education personnel is: increasing professionalism, improving the quality of education, recognition and certification. Problems in implementing standards for educators and educational staff are: limited flexibility, lack of facilities and training for educators in the regions, heavy administrative burden. Solutions: flexibility in standards, improved educational infrastructure and facilities, increased access to training and certification, reduced administrative burden.